Causal impacts of epidemics and pandemics on food supply chains: A systematic review - Cardoso, Brenda (2021)
The epidemics and pandemics can severely affect food supply chains, including producers, retailers, wholesalers, and customers. To minimize their impacts, it is fundamental to implement effective policies that ensure continuity in the provision, affordability, and distribution of basic food items. This research identifies the main impacts of pandemics and epidemics on food supply chains and policies that can minimize these impacts. Based on a systematic literature review (SLR), 173 documents are analysed to propose a taxonomy of impacts on four supply chain links: demand-side, supply-side, logistics and infrastructure, and management and operation. The taxonomy presents the main impacts and respective mitigation policies. In addition, the literature review leads to the development of a comprehensive causal loop diagram (CLD) with the identification of main variables and their relationship with food supply chains. Finally, a specific research agenda is proposed by identifying the main research gaps. These findings provide a structured method for evaluating policies that ensure the functioning of food supply chains, particularly in disruptions such as epidemics and pandemics.